Universal human rights in theory and practice - Donnelly, Jack (Rawat Publications, 2014)
In the third edition of his classic work, revised extensively and updated to include recent developments on the international scene, international studies professor Jack Donnelly explains and defends a richly interdisciplinary account of human rights as universal rights. He shows that any conception of human rights--and the idea of human rights itself--is historically specific and contingent. Since publication of the first edition in 1989, this book has justified Donnelly's claim that "conceptual clarity, the fruit of sound theory, can facilitate action. At the very least it can help to unmask the arguments of dictators and their allies."--Adapted from back cover.